Lockdown Social Isolation and Lockdown Stress During the COVID-19 Pandemic in China: The Impact of Mindfulness - Li, Jianfeng; Zhou, Luyang; Van der Heijden, Beatrice; Li, Shengxiao; Tao, Hong; Guo, Zhiwen (Frontiers in Psychology, 2022)
This study is aimed to examine the impact of mindfulness in the relationship between social isolation, job and financial insecurity, and stress during the lockdown period of the COVID-19 pandemic. Drawing on Conservation of Resources theory, Psychological Contract theory, Mindfulness theory, and Awareness notion, we propose that lockdown job insecurity partially mediates the relationship between lockdown social isolation and lockdown financial insecurity, and that the relationship between lockdown social isolation and lockdown stress is mediated as follows: first, simple partial mediation through both lockdown job and financial insecurity and second, sequential mediation through lockdown job and financial insecurity. Moreover, we assume that mindfulness moderates the relationship between lockdown financial insecurity and lockdown stress. The results from our Structural Equation Modeling analyses, using a sample of 1,356 Chinese respondents, indicate that all of our research hypotheses are confirmed. From this empirical work, it becomes clear that mindfulness, which is believed by many people to be able to reduce stress during the COVID-19 lockdown period, in fact is endangering their mental health (that is, they experience more stress) instead. This article concludes with theoretical and practical implications of our study, followed by its limitations and recommendations for future research.